Effects of mix herbs topical and oral therapies on diabetic foot ulcers: a case report - Haryanto, Haryanto; Gusmiah, Tisa; Makmuriana, Lestari; Wuriani, Wuriani (Universitas Muhammadiyah Purwokerto, 2019)
Background: Indonesia is a tropical country with lots of potential-therapy resource plants, including those for wound care like honey, sea cucumber, black seed and aloe vera. There are other complementaries used by oral such as Radix Rehmanniae Preparata, Panix Ginseng and Gypsum Florosum.Case presentation: This study case reported the effectiveness of complementary herbs by topical and oral for two patients with diabetic foot given on the wound area.Conclusion: The result revealed that mix herbs (radix rhamanniae, panax ginseng and gypsum florosum) by oral and topical (natural honey, black seed and sea cucumber) could heal diabetic foot ulcers.